The shooting at Château Rock - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series, 2020)
"It's summer in the Dordogne. The heirs of a Périgordian sheep farmer learn that they have been disinherited, and their father's estate sold to an insurance company in return for a policy that will place him in a five-star retirement home for the rest of his life. But the farmer never gets his life of luxury - he dies before moving in. Was it a natural death? Was there foul play? Bruno begins the investigation that leads him to several shadowy insurance companies owned by a Russian oligarch with a Cypriot passport. The companies are based in Cyprus, Malta, and Luxembourg, but Bruno finds a weak spot in France: the Russian's France-based notaire and insurance agent. As Bruno is pursuing this lead, the oligarch's daughter turns up in the Périgord, and complications ensue, eventually bringing the action to the château of an aging rock star. But, as ever, Bruno makes time for lunch amid it all." -- Provided by publisher.